Hydrogen sulfide generated by L-cysteine desulfhydrase acts upstream of nitric oxide to modulate abscisic acid-dependent stomatal closure - Scuffi, Denise (2014)
Abscisic acid (ABA) is a well-studied regulator of stomatal movement. Hydrogen sulfide (H2S), a small signaling gas molecule involved in key physiological processes in mammals, has been recently reported as a new component of theABA signaling network in stomatal guard cells. In Arabidopsis (Arabidopsis thaliana), H2S is enzymatically produced in the cytosol through the activity of L-cysteine desulfhydrase (DES1). In this work, we used DES1 knockout Arabidopsis mutant plants (des1) to study the participation of DES1 in the cross talk between H2S and nitric oxide (NO) in the ABA-dependent signaling network in guard cells. The results show that ABA did not close the stomata in isolated epidermal strips of des1 mutants, an effect that was restored by the application of exogenous H2S. Quantitative reverse transcription polymerase chain reaction analysis demonstrated that ABA induces DES1 expression in guard cell-enriched RNA extracts from wild-type Arabidopsis plants. Furthermore, stomata from isolated epidermal strips of Arabidopsis ABA receptor mutant pyrabactin-resistant1(pyr1)/pyrabactin-like1 (pyl1)/pyl2/pyl4 close in response to exogenous H2S, suggesting that this gasotransmitter is acting downstream, although acting independently of the ABA receptor cannot be ruled out with this data. However, the Arabidopsis clade-A PROTEIN PHOSPHATASE2C mutant abscisic acid-insensitive1 (abi1-1) does not close the stomata when epidermal strips were treated with H2S, suggesting that H2S required a functional ABI1. Further studies to unravel the cross talk between H2S and NO indicate that (1) H2S promotes NOproduction, (2) DES1 is required for ABA-dependent NO production, and (3) NO is downstream of H2S in ABA-induced stomatal closure. Altogether, data indicate that DES1 is a unique component of ABA signaling in guard cells.